Pengaruh Implementasi Problem-Based Learning (PBL) Terhadap Pembelajaran Procedural Text Dan Berpikir Kritis Di Kelas VIII SMP Nusantara Palangka Raya - Ristati; Maida Norahmi; Novika Amalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
The innovative learning model Problem Based Learning (PBL) will be applied to overcome the problems faced by students of class VIII, SMP Nusantara Palangka Raya. The problem is the lack of students' ability to understand procedural text and the lack of students' ability to think critically. This research is an experiment with pre-test -> treatment -> post-test design. The instruments used to collect data are interviews, questionnaires, and tests. Data analysis using SPSS. The results showed there was a significant increase from the pretest variable to the posttest variable after receiving treatment, (pretestM = 69.1, SD = 5.527; posttest M = 88.1, SD = 8,478; t(9)=-13,217, p=.000). Then the correlation coefficient value or correlation is 0.872 with a sig value. 0.001 < 0.05. The results of the paired sample test show the value of Sig. (2-tailed) is 0.000 < 0.05, and the Mean Paired Difference value is -19.000. Since Ha is accepted, these results shown that there is an increase in the understanding of procedural texts through the application of the PBL model and the critical thinking skills of grade VIII students of SMP Nusantara Palangka Raya. Therefore, this study recommends the application of PBL to improve students’ performance.